2008
DOI: 10.7326/0003-4819-149-11-200812020-00004
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Screening Scores and Medication Nonadherence

Abstract: Alcohol misuse, as measured by a brief screening questionnaire, was associated with increased risk for medication nonadherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
92
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(105 citation statements)
references
References 42 publications
8
92
1
4
Order By: Relevance
“…The majority of patients on statins do not abuse alcohol. It was shown that alcohol misuse was associated with increased risk for statin non-adherence [103,104]. It can be assumed that high doses of alcohol provoke liver dysfunction and increase the risk of myopathy in patients on high-intensity statin therapy [104].…”
Section: Alcohol Consumption and Statin Intolerancementioning
confidence: 99%
“…The majority of patients on statins do not abuse alcohol. It was shown that alcohol misuse was associated with increased risk for statin non-adherence [103,104]. It can be assumed that high doses of alcohol provoke liver dysfunction and increase the risk of myopathy in patients on high-intensity statin therapy [104].…”
Section: Alcohol Consumption and Statin Intolerancementioning
confidence: 99%
“…Based on the recent work of Bradley and colleagues, 9 and on the fact that low-level drinkers have lower risk of death and other medical problems than non-drinkers, 5,6,8 we categorized AUDIT-C scores into four groups (0, 1-4, 5-8, and 9-12) with 1-4 as the reference group. Initial analyses described the sample, evaluated associations between each covariate and AUDIT-C group with chi-square tests, and calculated the unadjusted prevalence of the outcomes in each AUDIT-C group.…”
Section: Analysis Strategymentioning
confidence: 99%
“…The Alcohol Use Disorders Identification Test-Consumption (AUDIT-C) is a screen of alcohol misuse which evaluates quantity and frequency of alcohol consumption, and has been validated in medical settings. [4][5][6][7][8] AUDIT-C scores of 5 or greater ('hazardous drinking': e.g., 3 or more drinks per occasion, on four or more days per week) have been associated with increased risk for subsequent medical problems, including medication non-adherence, 9 fractures, 10 hospitalization for gastrointestinal illnesses, 11 and all-cause mortality. 12 Giving patients specific feedback about alcohol consumption, for example linking their drinking to health risks, can reduce hazardous alcohol use.…”
Section: Introductionmentioning
confidence: 99%
“…The AUDIT-C score (0-12 points) also reflects severity of symptoms due to unhealthy drinking. 28 In addition, AUDIT-C scores have been associated with increased risk for medication non-adherence (AUDIT-C scores ≥ 4), 29 hospitalizations for liver disease, upper gastrointestinal bleeding, or pancreatitis (≥ 6 for men in general; ≥ 4 for men under 50 years old), 30 fractures (≥ 8), 31 and death in men under 50 years old (≥ 10). 32 Therefore, AUDIT-C scores can assist providers to offer patients personalized feedback on alcoholrelated risks.…”
mentioning
confidence: 99%